Galunisertib modifies the liver fibrotic composition in the Abcb4Ko mouse model - Hammad, Seddik; Cavalcanti, Elisabetta; Werle-Urban, Julia; Caruso, Maria Lucia; Dropmann, Anne; Ignazzi, Antonia; Ebert, Matthias; Dooley, Steven; Giannelli, Gianluigi (Archives of toxicology, 2018)
Transforming growth factor (TGF)-β stimulates extracellular matrix (ECM) deposition during development of liver fibrosis and cirrhosis, the most important risk factor for the onset of hepatocellular carcinoma. In liver cancer, TGF-β is responsible for a more aggressive and invasive phenotype, orchestrating remodeling of the tumor microenvironment and triggering epithelial-mesenchymal transition of cancer cells. This is the scientific rationale for targeting the TGF-β pathway via a small molecule, galunisertib (intracellular inhibitor of ALK5) in clinical trials to treat liver cancer patients at an advanced disease stage. In this study, the hypothesis that galunisertib modifies the tissue microenvironment via inhibition of the TGF-β pathway is tested in an experimental preclinical model. At the age of 6 months, Abcb4ko mice-a well-established model for chronic liver disease development and progression-are treated twice daily with galunisertib (150 mg/kg) via oral gavage for 14 consecutive days. Two days after the last treatment, blood plasma and livers are harvested for further assessment, including fibrosis scoring and ECM components. The reduction of Smad2 phosphorylation in both parenchymal and non-parenchymal liver cells following galunisertib administration confirms the treatment effectiveness. Damage-related galunisertib does not change cell proliferation, macrophage numbers and leucocyte recruitment. Furthermore, no clear impact on the amount of fibrosis is evident, as documented by PicroSirius red and Gomori-trichome scoring. On the other hand, several fibrogenic genes, e.g., collagens (Col1α1 and Col1α2), Tgf-β1 and Timp1, mRNA levels are significantly downregulated by galunisertib administration when compared to controls. Most interestingly, ECM/stromal components, fibronectin and laminin-332, as well as the carcinogenic β-catenin pathway, are remarkably reduced by galunisertib-treated Abcb5ko mice. In conclusion, TGF-β inhibition by galunisertib interferes, to some extent, with chronic liver progression, not by reducing the stage of liver fibrosis as measured by different scoring systems, but rather by modulating the biochemical composition of the deposited ECM, likely affecting the fate of non-parenchymal cells.